Extraarticular distal humeral nonunion: systematic review of literature - Vicenti, Giovanni; Guerra, Enrico; Pesare, Elisa; Colasuonno, Giulia; Minerba, Marco; Loiodice, Michele; Conte, Francesco; Sergi, Paolo; Solarino, Giuseppe (Journal of orthopaedics and traumatology, 2025)
Background Distal humeral fractures accounted for ~1% of all fractures; however, they were prone to complications, including nonunion if left untreated or inadequately managed. Nonunion, which predominantly occurred at the supracondylar level, resulted in mechanical instability, functional impairment, and persistent discomfort. The most commonly employed surgical options included open reduction and internal fixation (ORIF), total elbow arthroplasty (TEA), and external fixation. This article provides a comprehensive assessment of these surgical procedures and shared clinical experiences related to these challenging cases. Methods A systematic review of literature was conducted using the PubMed database up to October 2024, with a focus on cases involving extraarticular distal humeral nonunions that were treated with ORIF, TEA, or Ilizarov techniques. Results A total of 25 studies involving 448 patients were encompassed in the review, with a mean patient age of 50 years and an average follow-up period of 48 months. Reported success rates for ORIF and TEA were 90% and 74%, respectively. A higher rate of fracture healing was demonstrated by ORIF, although functional outcomes were found to be comparable between the techniques. Complications such as infections and reduced range of motion (ROM) were documented. Conclusions The highest success rate in treating aseptic nonunions was associated with ORIF, highlighting the importance of stable fixation, bone grafting, and meticulous preoperative planning. TEA was regarded as a viable option, particularly for patients with poor bone quality or complex, unreconstructible fractures. To optimize outcomes, surgical techniques were required to be customized on the basis of patient-specific factors and surgeon expertise. Further research is recommended to facilitate the comparison of long-term functional outcomes across different surgical approaches. Level of evidence : IV.